2002
DOI: 10.1038/sj.bjp.0704489
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of nitric oxide generation from nitroglycerin and endogenous sources during hypoxia in vivo

Abstract: 1 Nitroglycerin (GTN), often used in conditions of cardiovascular ischaemia, acts through the liberation of nitric oxide (NO) and the local concentration of NO in the tissue is responsible for any biological eect. However, little is known about the way in which the concentration of NO from GTN and other NO-donors is in¯uenced by low oxygen tension in the target tissues. 2 To evaluate the impact of changes in oxygen tension in the metabolism of NO-donors we measured exhaled NO in anaesthetized rabbits in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 48 publications
2
45
0
Order By: Relevance
“…These results suggest that hypoxic enhancement of Ca 2ϩ sensitivity in IPA was due to hypoxic inhibition of NO production or activity in smooth muscle. Consistent with this possibility, all three NOS isoforms (neuronal, inducible, and endothelial) have been detected in PASMC (12, 17, 49, 67, 71, 76, 78 -80), and hypoxic inhibition of NO production or its transduction pathways has been reported in isolated pulmonary arteries (19,28,55,63) and isolated (1,7,9,11,20,24,29,44) and intact (1,13,60) lungs.…”
Section: Discussionsupporting
confidence: 52%
“…These results suggest that hypoxic enhancement of Ca 2ϩ sensitivity in IPA was due to hypoxic inhibition of NO production or activity in smooth muscle. Consistent with this possibility, all three NOS isoforms (neuronal, inducible, and endothelial) have been detected in PASMC (12, 17, 49, 67, 71, 76, 78 -80), and hypoxic inhibition of NO production or its transduction pathways has been reported in isolated pulmonary arteries (19,28,55,63) and isolated (1,7,9,11,20,24,29,44) and intact (1,13,60) lungs.…”
Section: Discussionsupporting
confidence: 52%
“…Our in vitro studies showed that incubation in the presence of GTN increased the sensitivity to doxorubicin and paclitaxel in cells exposed to hypoxia but not in cells at 20% O 2 . It has been reported that the biotransformation of GTN is increased under hypoxic conditions (19,41). Therefore, GTN may represent an important and useful agent for selectively targeting the more malignant hypoxic cells.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 This idea is based on reports, both in vitro and in vivo, [3][4][5][6][7] that suggest that exposure to GTN leads to the formation of NO. However, in most of these studies, NO was observed only when GTN concentrations considerably exceeded the plasma levels reached during clinical dosing, whereas a number of further reports question the direct formation of NO.…”
mentioning
confidence: 99%